Translation of the working alliance inventory short revised into Italian using a Delphi procedure and a forward-backward translation - Buono, Nicola; Sassier, Béatrice; Thulesius, Hans; Hoffman, Robert; Nabbe, Patrice; Petek, Davorina; Le Reste, Jean Yves (Frontiers in Medicine, 2024)
Introduction: Enhancing treatment adherence, especially for chronic diseases, can be achieved through therapeutic alliance, potentially elevating the quality of care. An instrument to evaluate the therapeutic alliance could be beneficial in routine clinical settings, educational environments, and extensive research efforts at national and European levels. In this study, we translated therapist and patient versions of the Working Alliance Inventory Short Revised (WAI-SR) into Italian. Methodology: An email-based Delphi method was employed for the English-to-Italian translation, incorporating a forward-backward process. The initial translation team comprised two Italian family physicians proficient in English, a linguist, and a psychiatrist. The forward translation was then reviewed by 18 Italian family physicians through a Delphi process and was subjected to a backward translation by two Italian English teachers. A cultural correspondence was subsequently identified to adjust translations within a national and international framework. Results: All 18 experts fully engaged in the Delphi process, and consensus was achieved by the second Delphi round. A cultural check checked for discrepancies regarding linguistic consistency with other translations and found no difference. Conclusion: This Italian translation of the WAI-SR is expected to support Italian family physicians aiming to enhance their clinical practice and therapeutic outcomes. It could also be a valuable tool for Italian medical students to foster therapeutic relationships and improve their communication skills.